2015
DOI: 10.1007/s13142-015-0341-0
|View full text |Cite
|
Sign up to set email alerts
|

A review of diabetes prevention program translations: use of cultural adaptation and implementation research

Abstract: The Diabetes Prevention Program (DPP) has been shown to prevent type 2 diabetes through lifestyle modification. The purpose of this study was to describe the literature on DPP translation, synthesizing studies using cultural adaptation and implementation research. A systematic search was conducted. Original studies evaluating DPP implementation and/or cultural adaptation were included. Data about cultural adaptation, implementation outcomes, and translation strategies was abstracted. A total of 44 were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 85 publications
3
91
0
Order By: Relevance
“…To our knowledge, this is the first digital translation of DPP for an underserved patient population. A recent review found that among the 15 DPP translation studies, only one was conducted in a primary care clinical setting [24]. Our study makes important additions to the body of literature on translation of DPP in the real-world by providing specific recommendations about how the recruitment and initial enrollment process might be better completed within safety net clinical sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first digital translation of DPP for an underserved patient population. A recent review found that among the 15 DPP translation studies, only one was conducted in a primary care clinical setting [24]. Our study makes important additions to the body of literature on translation of DPP in the real-world by providing specific recommendations about how the recruitment and initial enrollment process might be better completed within safety net clinical sites.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have translated DPP to real-world community settings (e.g., YMCA, churches, or workplace) and clinical settings that required cultural adaptation of the program [24, 25]. To our knowledge, this is the first digital translation of DPP for an underserved patient population.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely translated and evaluated diabetes prevention program is the US DPP. A 2015 systematic review found 44 studies evaluating the US DPP across a range of settings and populations including various minority groups and populations with low socio-economic status [59]. The Centers for Disease Control and Prevention (CDC) have now developed a curriculum to ensure adapted US DPP programs meet requirements for recognition including complying with the Standards and Operating Procedures [60] and as well as completing a capacity assessment to ensure organizations are able to start and maintain programs successfully.…”
Section: Discussionmentioning
confidence: 99%
“…DPP‐based studies were conducted in various settings. Participants included minority and low‐income members of society . In the EU, the Finnish DPS study was translated in other areas .…”
Section: Question 2: How Does a Diabetes Prevention Program Effectivementioning
confidence: 99%